Project ECHO®: a global cross-sectional examination of implementation success - Perrin Moss; Nicole Hartley; Trevor Russell (BMC, 2024)
Abstract Background Organizations implement innovations to disrupt the status quo and create value. Within sectors such as healthcare, innovations need to navigate large scale system and organizational factors to succeed. This research explores the implementation of a global innovation- Project ECHO®. Project ECHO® is a validated virtual communities of practice model organizational teams implement to build workforce capacity and capability. Project ECHO® has experienced broad global adoption, particularly within the healthcare sector, and is experiencing growth across other sectors. This study sought to examine the state of implementation success for Project ECHO® globally, to understand how these implementations compare across geographic and sectoral contexts, and understand what enablers/barriers exist for organizational teams implementing the innovation. Methods An empirical study was conducted to collect data on 54 Project ECHO® implementation success indicators across an international sample. An online survey questionnaire was developed and distributed to all Project ECHO® hub organizations globally to collect data. Data was analyzed using descriptive statistics. Results The 54 implementation success indicators measured in this survey revealed that the adoption of Project ECHO® across 13 organizations varied on a case-by-case basis, with a strong rate of adoption within the healthcare sector. Implementation teams from these organizations successfully implemented Project ECHO® within 12-18 months after completing Immersion partner launch training and operated 51 ECHO® Networks at the time of data collection. Implementation teams which liaised more regularly with ECHO® Superhub mentors often went on to launch a higher number of ECHO® Networks that were sustained over the longer term. This suggests that these implementation teams better aligned and consolidated their Project ECHO® pilots as new innovations within the local context and strategic organizational priorities. Access to research and evaluation capability, and a more automated digital client relationship management system were key limitations to showcasing implementation success outcomes experienced by the majority of implementation teams. Conclusions These findings make a valuable contribution to address a knowledge gap regarding how a global sample of organizations adopting Project ECHO® measured and reported their implementation successes. Key successes included pre-launch experimentation and expansion, Superhub mentorship, stakeholder engagement, and alignment to strategic priorities.